S SISTEM PAKAR DIAGNOSA KERUSAKAN MOTOR KAWASAKI KLX150 MENGGUNAKAN METODE CASE-BASED REASONING DENGAN ALGORITMA 3W-JACCARD - Edwin Febriansyah; Edy Winarno (JURNAL ILMIAH INFORMATIKA, 2021)
In this day and age, motorbikes have an important role in transportation facilities, motorbike users are increasingly dense, especially in the city of Semarang, which is not accompanied by information media. The lack of media information regarding damage to the motorbike makes it difficult for someone to know the cause of the damage to the motorbike, not to mention the Kawasaki KLX150 which happens a lot of engine damage. For this reason, the expert system diagnoses motor damage by knowing the type of motor damage, after that diagnostics and alternative solutions to the problem are carried out. With this, the method and algorithm used is Case-Based Reasoning (CBR) using the Similarity 3W-Jaccard calculation, this second method and algorithm can be used to diagnose damage from the symptoms in the database. Each symptom has a weighted value of each, including a value of 5 (five) for severe symptoms, relating to engine and electrical parts, a value of 3 (three) for moderate symptoms, relating to braking and chains, a value of 1 (one) mild symptom, relating to with the indicator on the speedometer. The system will display 5 (five) types of damage calculated using the 3W-Jaccard Algorithm sorted by the highest value. The revision process will appear if the similarity calculation results are less than 0.6 (zero point six) because it is considered that the results are not sufficiently similar to the solution to be repaired, it needs to be reviewed and will be entered into the review table, then the expert will find a solution.